INFLUENCES OF GRINDING PROCESS ON THE PHYSICAL AND MORPHOLOGICAL CHARACTERISTICS OF ULTRAFINE TREATED RICE HUSK ASH - Saad S.A.; Jamaluddin A.N.; Masjuki S.A.; Beddu S.; Shafiq N. (GEOMATE International Society, 2023)
This paper aims to extend the investigation of producing highly reactive additive material in ultrafine size, with a particle diameter of less than 5?m through mechanical activation using a planetary ball mill. In light of the mechanical activation process, most studies were done to test materials such as metakaolin and fly ash. However, studies on the mechanical activation effect via planetary ball mill to conventional RHA or treated RHA are limited. In this research, raw rice husk (RH) was treated using a low heated concentration of acid, i.e., 0.01 - 0.1M hydrochloric acid (HCl). Then, the treated RH was combusted at 600 - 800o C. Finally, the treated RHA was ground using a planetary ball mill for 15 - 60 minutes. As a result, it was also observed that a burning temperature of 600, treated at four hours and ground at 300rpm for 15 minutes, had the finest size of ultrafine treated RHA (UFTRHA) with an average particle size value (D50) of 4.012m. Furthermore, the largest specific surface area (SSA) value was obtained at 222.9125 m2 /g with a similar treatment condition. Concerning the UFTRHA morphology, particle agglomeration was observed for samples with a grinding duration of more than 15 minutes. Therefore, grinding parameters involved in the process are proven to affect the physical and morphological attributes of UFTRHA produced. Particle size reduction and significant SSA value of UFTRHA are vital for effective pozzolanic reaction and hence promote a greater material performance as a superior additive in concrete application. Int. J. of GEOMATE All rights reserved, including making copies unless permission is obtained from the copyright proprietors.